(untitled) (Ameghiniana, 2013)
A new species of the genus Eurydesma (E. harringtoni) is described from Patagonia. Some paleoecological aspects of the species are analized, and the filogeny of the family Eurydesmidae it briefly considered. An upper carboniferous age is stablished for the fossil remain, based on the brachiopod Levipustula and bryozcans within the Levipustula zone.